Pengaruh Motivasi Kerja Dan Employee Engagement Terhadap Kinerja Karyawan Pt. Xyz - Jely Aulia Zahra; Siska Lusia Putri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
of work motivation and employee engagement on employee performance. This research is quantitative in nature, and the data collection methods used are questionnaires and interviews. The population in this study consists of all employees of PT XYZ, totaling 32 people. The sample size taken in this study is 32 employees. The sampling technique used in this study is a census or saturated sampling, where the entire population is used as the sample. Based on the research findings and data analysis using SPSS (Statistical Product and Service Solutions), the results show that: (1) Work motivation has a positive and significant influence on employee performance. (2) Employee engagement has a positive and significant influence on employee performance. (3) Work motivation and employee engagement together have a positive and significant influence on employee performance. The implication of these conclusions is that efforts to improve employee performance at PT XYZ should focus on enhancing work motivation and employee engagement so that employee performance can also improve.